Eficácia do PECS-Adaptado quando aplicado por mães em crianças com autismo em diferentes contextos - Ribeiro, Karina Ferreira (2020)
The present study aims to apply and evaluate the effectiveness of the Adapted PECS (Engaged People Communicating Socially) applied by mothers of children with autism with impaired functional language in a family context. The influence of training in other contexts on the mother's behavior was also evaluated, through the design of multiple probes by condition. Three mothers and their children with autism, aged between 4 and 11 years participated in the research. Theoretical and practical training was carried out with the children's mothers, so that Alternative Communication could be defined, as well as it’s importance and use in different contexts. After the intervention, the use of the communication system by mothers in two other contexts different from the domestic context was analyzed, these being other contexts, environments in which the child feels at ease, such as ice cream and park. The independent variable is the intervention itself through the Adapted PECS and the dependent variable is the mothers’ performance in generalizing the new communicative medium to other social contexts. From the intervention carried out at home with the three participating mothers, it can be concluded that all of them were able to learn to communicate with their children through the PECS-Adapted and generalized this ability to the other two environments analyzed. Likewise, two of the three participating children were able to generalize, from training at home, also to the other two environments. Two children started to verbalize, preferring this mode of communication from the moment they acquired this skill.